Development and psychometric properties of the transphobia scale among Indian adolescents - Yashwee Lonkar; Pushpalata Sharma; Jyoti Janswamy; Ruchi Sachan; Mahendra Kumar (JKP (Jurnal Keperawatan Padjajaran), 2023)
Background: Most of the studies employed in the concerning area use foreign scales or translated versions for measurement of transphobia. It isreally unfortunate a democratic country like India does not possesses anystandardized scale to measure the transphobia of adolescents.